Legal and Institutional Framework on Counter-Terrorism in Indonesia - Sri Suatmiati; Edy Kastro (Jurnal Media Hukum, 2020)
The current legal basis for combating terrorism in Indonesia is The Government Regulations in Lieu of Statute (Perpu) No. 1 of 2002 on the Eradication of Terrorism. The fight against terrorism involves various institutions including national police, national army, and civil society. With regard to this, special unit has been established to deal with terrorism by national police and national army as well. This paper aims at elaborating the legal and institutional framework for combating terrorism in Indonesia and the possible way to improve it. This normative legal research employs statutory approach. It is found that basically the existing law has been strong enough. However, the eradication of terrorism would be more effective if Indonesia adopt preventive detention clause as governed under the Internal Security Act (ISA) in Singapore and Malaysia. This clause allows the authority to detain the suspect without legal process when his action is considered as the threat of national security.